RUSSIAN LANGUAGE UNITS IN A SPANISH LITERARY TEXT: PRAGMATIC AND COGNITIVE POTENTIAL - Irina R. Abkadyrova (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2022)
The purpose of the study is to identify the semantic and cognitive-pragmatic features of the implementation of Russian language units in the novel “Testigo invisible” by K. Posadas. The analysis showed that the semantic and cognitive-pragmatic potential of Russian language units in the analyzed literary text differs from their potentials for the bearer of the Russian-speaking culture. Comments are introduced to complete lacunar implicatures. At the same time, the Spanish-speaking reader receives only the relevant component of the meaning of the units: the pragmatic vector of information presentation determines a certain perception of the units by the reader.